PENGARUH PENAGIHAN PAJAK AKTIF TERHADAP PENERIMAAN PAJAK DI KANTOR PELAYANAN PAJAK PRATAMA MEDAN BELAWAN - Farida Khairani Lubis (Universitas Islam Islam Sumatera Utara, 2019)
This research has a purpose that affects the active tax collection against the delinquency of tax arrears in the field of primary tax service Medan Belawan, partially and simultaneously. Tax arrears are dependent variable and the active tax collection is an independent variable consisting of a letter of reprimand and a forced letter. This research uses a Likert scale in data collection. With a total population of 235 the taxpayers at the Tax Service office Medan Belawan. And the number of samples selected as much as 148 people. Technical analysis of data used in the form of validity test, reliability test, classical assumption test, double linear regression test, hypothesis test and coefficient of determination test.This the result of this study was seen in a partial reprimand letter and the forced letter had an influence on the tax arrears on the primary Tax Service office of Medan Belawan. Simultaneously that the letter of reprimand and forced letter together has a significant influence on the tax arrears in the primary tax servant office of Medan Belawan.